Gag and protease co-evolution modeling for HIV-1 - Wang, Junjie (2014)
Gag and Protease play important roles in the lifecycle of the HIV-1 virus. Protease is the viral enzyme that cleaves Gag to form functional Gag subunits during the viral maturation. To interfere with the maturation of the HIV virus, Protease Inhibitors or drugs are used to inhibit the Gag-cleaving function of Protease. However, during the viral evolution, while mutations of both Gag and protease that are resistant to most of the current drugs have been reported, co-evolution relationship of Gag and Protease is limitedly studied. Therefore, understanding this relationship between Gag and Protease is crucial for finding a strategy in HIV treatment.